2010
DOI: 10.1136/bmj.b5465
|View full text |Cite
|
Sign up to set email alerts
|

Use of angiotensin receptor blockers and risk of dementia in a predominantly male population: prospective cohort analysis

Abstract: Objective To investigate whether angiotensin receptor blockers protect against Alzheimer's disease and dementia or reduce the progression of both diseases. Design Prospective cohort analysis. Setting Administrative database of the US Veteran Affairs, 2002-6. Population 819 491 predominantly male participants (98%) aged 65 or more with cardiovascular disease. Main outcome measures Time to incident Alzheimer's disease or dementia in three cohorts (angiotensin receptor blockers, lisinopril, and other cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
346
3
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(382 citation statements)
references
References 61 publications
(65 reference statements)
23
346
3
10
Order By: Relevance
“…Similar beneficial effects in reducing the incidence and/or AD progression, has been found in a clinical trial with angiotensin 1 (AT-1) receptor blocker (Li et al 2010). Although experiments in animal AD models are limited, the results support the findings from clinical trials.…”
Section: Antihypertensive Drugssupporting
confidence: 71%
“…Similar beneficial effects in reducing the incidence and/or AD progression, has been found in a clinical trial with angiotensin 1 (AT-1) receptor blocker (Li et al 2010). Although experiments in animal AD models are limited, the results support the findings from clinical trials.…”
Section: Antihypertensive Drugssupporting
confidence: 71%
“…20 ARB treatment has also been linked to a reduced risk of Alzheimer disease among persons with a history of CVD, as compared with other cardiovascular drugs; however, this analysis used administrative data without validated outcome assessment and did not assess BB use specifically. 29 In an autopsy series of hypertensive subjects, ARB use was associated with less Alzheimerrelated pathology but more strokes, as compared with other antihypertensive and no drug treatment, although BB use alone was not evaluated. 30 Clinical trial data are similarly limited.…”
Section: Resultsmentioning
confidence: 99%
“…Medication with ARBs has been associated with decreased incidence of dementia [109,110]. Epidemiological analyses revealed that a group of patients that took ARBs, displayed significantly reduced incidence and progression of AD and dementia than those treated with a comparable antihypertensive agent, ACE inhibitor [109].…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Medication with ARBs has been associated with decreased incidence of dementia [109,110]. Epidemiological analyses revealed that a group of patients that took ARBs, displayed significantly reduced incidence and progression of AD and dementia than those treated with a comparable antihypertensive agent, ACE inhibitor [109]. In vivo animal studies revealed that oral or intranasal administration of some ARBs, including valsartan, olmesartan, and losartan, reduced Aβ levels and ameliorated spatial learning and memory deficits in mouse models of Aβ pathology [111,112].…”
Section: Antihypertensive Drugsmentioning
confidence: 99%